Analisis Prediksi Bangkitan Perjalanan akibat Pembangunan Perumahan Subsidi di Kecamatan Baturaja Timur Terhadap Kinerja Jaringan Jalan - Yuni Widia Sari (UNIVERSITAS LAMPUNG, 2019)
Transportation problems in residential areas arise because of the movement patterns of people and goods and the development of land areas that are not in accordance with the capacity of the road network performance. In this case if the influence of the road network is not considered it will have an impact on the level of road services to be low, causing congestion, increasing the number of accidents, traffic violations and the function of the road itself. The development of subsidized housing aimed at low-income people in East Baturaja District has increased since 2017 with 722 houses. That is, with the increase in development can have an impact on housing traffic with the performance of the road network. The purpose of this study is to predict trip generation due to the construction of subsidized housing on the performance of the road network of subsidized housing areas in East Baturaja District. The problem in this study is knowing the character - istics of the respondents, then determining the variables that become the benchmark in this study are the Purpose of Leaving the House (X1), Total Revenue (X2), Total Expenditures (X3), Types of Transportation Modes Used (X4), Ownership Motorcycle (X5), Car Ownership (X6) and Transportation Costs (X7). The study uses quantitative methods and multiple linear regression analysis with sampling using a tiered formula and the proportional formula to take samples so that some regions are represented as many as 135 samples. From the results of the study there are four variables that meet, namely, X1, X2, X4, X2 and obtained the equation Y = -1.07 + 0.13 (X1) + 0.19 (X2) + 0.20 (X4) + 0.73 ( X5) and the price R2 = 0.79 is obtained. The effect of the trip generation on the road network is: 102.5 pcu / hour.